Effect of naproxen on oxidative stress biomarkers in Gammarus pulex - Engin Seker (Revista Científica)
Non–steroidal anti–inflammatory drugs (NSAIDs) are a widely prescribed medication class that is used in the treatment of numerous conditions worldwide. Of these drugs, naproxen is the most commonly used NSAID. Following administration, non–steroidal anti–inflammatory drugs (NSAIDs) such as naproxen are eliminated from the body in either their original chemical form or as metabolites, ultimately entering the aquatic environment. The current study sought to show the impacts of naproxen on the oxidant/antioxidant status of Gammarus pulex, an aquatic invertebrate (Amphipoda). Gammarus pulex were exposed to sublethal concentrations of naproxen (3.44, 6.87 and 13.75 mg·L-1) for 96 hours (h). Whole body tissue samples were collected after 24, 48 and 96 h of exposure and analysed to determine the oxidant/antioxidant status by quantifying malondialdehyde (MDA) and total glutathione levels (GSH), and superoxide dismutase (SOD), and catalase (CAT) activities of the G. pulex. The level of MDA exhibited a remarkable increase, while the endogenous GSH level showed a significant depletion in tested whole body tissues in a time–dependent manner after naproxen treatment of G. pulex. In G. pulex exposed to the highest dose of naproxen; decreases in GSH activity, SOD and CAT activities were observed.The SOD activity did not show a discernible rise in statistics after 24 and 48 h of exposure, however, a difference was observed after 96 h compared to the control group (P<0.05). The findings of this study demonstrated the capacity of naproxen to initiate oxidative stress and elevate MDA levels in G. pulex, even at remarkably low concentrations. This study emphasizes that it is essential to develop effective methodologies to impede naproxen entry into the aquatic environment.